2014
DOI: 10.1039/c3ce42638f
|View full text |Cite
|
Sign up to set email alerts
|

Growth evolution of SixNy on the GaN underlayer and its effects on GaN-on-Si (111) heteroepitaxial quality

Abstract: We verified that nanocrystalline SixNy with a size ranging from 4 to 6 nm appeared on the pit sidewall and preferred to reside at the pit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…These results indicated that the SLs can effectively assist in the elimination of dislocations. The screw and edge dislocation densities (D screw and D edge ) can be derived from the following equations: D screw = β (002) /9b 2 screw and D edge = β (102) /9b 2 edge 16 . In these two equations, β (002) and β (102) represent the FWHM values of AlN(0002) and AlN(10ī2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the SLs can effectively assist in the elimination of dislocations. The screw and edge dislocation densities (D screw and D edge ) can be derived from the following equations: D screw = β (002) /9b 2 screw and D edge = β (102) /9b 2 edge 16 . In these two equations, β (002) and β (102) represent the FWHM values of AlN(0002) and AlN(10ī2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Recently, we have demonstrated high-quality In 0.3 Ga 0.7 As epitaxial layers on a 2 nm amorphous In 0.6 Ga 0.4 As buffer layer on GaAs substrate by means of low-temperature molecular beam epitaxy (LT-MBE). 15 An amorphous In 0.6 Ga 0.4 As insert layer can be utilized as an elastic layer between the In 0.3 Ga 0.7 As epilayer and the GaAs substrate.…”
Section: Introductionsmentioning
confidence: 99%
“…These are vital for improving the performance of devices on Si. To date, high-quality group III-nitride thin films have been achieved on Si substrates by PLD [147,[154][155][156][157][158][159][160][161][162][163][164]. (111) substrates at various temperatures ranging from 300 to 750 1C [165].…”
Section: Group Iii-nitride Films On Cu Substrates By Pldmentioning
confidence: 99%